Analisis Miskonsepsi Pada Materi Suhu dan Kalor Menggunakan Metode CRI - fima ratna sari; Syuhendri Syuhendri; Leni Marlina (Jurnal Ilmu Fisika dan Pembelajarannya (JIFP), 2022)
This study aims to analyze the misconceptions that occur in the material of temperature and heat, high school students in class XI IPA1. The research design used survey research with sampling using simple random sampling. The research data were obtained through a multiple-choice test of concept questions with a response index certainty answer sheet (CRI, and open interviews with 3 students. The sample was collected again by 20 students of SMAN 2 OKU. The findings of this study are, the misconceptions contained in each temperature sub-concept and heat. The highest percentage of misconceptions is found in the increase sub-concept by 53.3% with the medium misconception category, and the lowest is in the heat transfer sub-concept by 20% with the low misconception category. It has been found that the causes of misconceptions, among others, students rarely get teaching about the concept, wrong prior knowledge, counting and memorizing, and teachers who teach also facilitate students to think analytically Teachers are expected to be able to change the process of learning activities into a meaningful process for students through varied methods and models, one way is by using student centered conceptual text learning.